Evaluation of Implementation of Semester Credit System through Independent Learning Activity Unit in State Senior High Schools in Malang City - husnul chotimah (Indonesian Journal of Natural Science Education, 2020)
Evaluation of implementation of semester credit system (SKS) through Independent Learning Activity Unit (UKBM) was aimed to generate an illustration which could be used as reference to make further policy for the implementation in State Senior High Schools in Malang City. The evaluation of SKS program through UKBM was based on the CIPP method and generated several results: 1) guide and illustrations of UKBM arrangement should be implemented in learning, 2) workshop on arranging UKBM should be organized by involving teachers from all subjects so that they could arrange and implement UKBM based learning, (3) existing UKBM should be revised, (4) sustained monitoring and evaluation on implementation process of learning through UKBM should be carried out by policy makers, (5) teachers should be approached so that learning through UKBM in SKS program would be carried out well and sustainably and (6) more attention should be given to students so that they could adjust themselves in learning through UKBM in SKS program.It is recommended that: (1) learning activities in the SKS program through the UKBM learning in State Senior High Schools in Malang City should be improved or reviewed, (2) students and teachers are not ready to carry out learning through UKBM in SKS program and (3) the improvement mentioned in the first suggestion could be carried out by rearranging and revising existing UKBM.